Magnetic activated carbon: A promising approach for the removal of methylene blue from wastewater - Dhilleswara Rao Vaddi; Ramanaiah Malla; satyanarayana Geddapu (Desalination and Water Treatment, 2024)
The contamination of water bodies by synthetic dyes, namely methylene blue (MB), is a significant environmental concern due to their contrary effects on aquatic ecosystems. This study proposes a novel approach by integrating magnetic properties into activated carbon to improve the removal efficiency of methylene blue and simplifies the separation process. The synthesis of magnetic activated carbon involved the impregnation of activated carbon (Rice husk as a precursor) with iron oxide nanoparticles ((Fe3O4-RAC), which imparted magnetic properties to the carbon matrix. The characterization studies were performed to perceive the morphology of the adsorbent. The adsorption tests were examined under various factors such as contact time, initial MB concentration, adsorbent dosage and pH. The data revealed that the equilibrium adsorption of methylene blue onto Fe3O4-RAC was achieved within 60 min, with a maximal adsorption strength of 32.25 mg g−1. The Langmuir model (R2 = 0.997) demonstrated the best fit, suggesting monolayer adsorption behaviour. Furthermore, the adsorption kinetics tailed pseudo-second-order (R2 = 0.995), indicating chemisorption as the rate-determining step. The results indicated a positive correlation between temperature and MB adsorption, signifying the endothermic nature. The magnetic properties of Fe3O4-RAC facilitated the separation of the adsorbent from the treated solution using an external magnetic field, eliminating the need for additional filtration or centrifugation steps. The regeneration of Fe3O4-RAC was also investigated, and it was found that the composite could be efficiently regenerated using ethanol as a desorption agent, allowing for repeated use. In conclusion, magnetic activated carbon demonstrated promising potential as an efficient and reusable adsorbent for the removal of methylene blue from wastewater.